Antifungal activities against mould and yeast strains - (:unkn) unknown (SOC LEATHER TECHNOL CHEMISTS, 1996)
The efficacy of three commercially available fungicides was determined on 20 fungal species and nine yeast species isolated from Turkish vegetable tanned sole leathers, chrome tanned hides (blue stock), 1-2 years and older chrome tanned leather, new and used shoes, and human feet. Each of the isolated organisms, whether fungi or yeast were treated with a series of dilutions of the fungicides to determine their relative effectiveness. The active ingredients of che commercially available fungicides were: isothiazoline and a quaternary ammonium compound (Fungicide A), benzthiazole (Fungicide B), and p-chloro-m-cresol with o-phenyl-phenol (Fungicide C). Fungal attack was controlled with Fungicide A al a 1:16 dilution, Fungicide B at 1:4 dilution, and Fungicide C at 1:32 dilution. II was found that Fungicide A and Fungicide C were more effective than Fungicide B in controlling fungal growth on leather, Fungicide A at 1:128 dilution, Fungicide B at 1:64 dilution and Fungicide C at 1:128 dilution exerted complete protection against yeast growth.